2021
DOI: 10.3389/fbuil.2021.660292
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of the Dynamic Response of Critical Zones in a Ballasted Railway Track

Abstract: The critical zones are the discontinuities along a railway line that are highly susceptible to differential settlement, due to an abrupt variation in the support conditions over a short span. Consequently, these zones require frequent maintenance to ensure adequate levels of passenger safety and comfort. A proper understanding of the behavior of railway tracks at critical zones is imperative to enhance their performance and reduce the frequency of costly maintenance operations. This paper investigates the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Te subgrades for the other two cases also show a similar increase in force per unit area compared to their respective subballasts. Tis signifes that the subgrade carries greater loads than the ballast or subballast when subjected to wheel loads [61] also showed that subgrade reactions to wheel loads are larger than subballast and ballast reactions.…”
Section: Efect Of Subballast Stifness On Vertical Stressmentioning
confidence: 97%
“…Te subgrades for the other two cases also show a similar increase in force per unit area compared to their respective subballasts. Tis signifes that the subgrade carries greater loads than the ballast or subballast when subjected to wheel loads [61] also showed that subgrade reactions to wheel loads are larger than subballast and ballast reactions.…”
Section: Efect Of Subballast Stifness On Vertical Stressmentioning
confidence: 97%
“…Sonlu elemanlar yönteminin demiryolu hatlarının yük altındaki davranışını analiz etmedeki etkinliği literatürde kanıtlanmıştır [24]. Demiryolu hatlarının davranışı geoteknik mühendisleri tarafından yaygın olarak kullanılan PLAXIS sonlu elemanlar programı ile iki ve üç boyutlu olarak araştırılmıştır [24,[28][29][30][31]. İki boyutlu analizler ile kıyaslandığında, üç boyutlu analizler daha fazla hesaplama süresine ihtiyaç duymaktadır.…”
Section: Nümeri̇k Anali̇zunclassified
“…Önceki çalışmalara uygun olarak, ray ve traversin modellenmesinde lineer elastik (LE) model kullanırken taban zemini ve alt balastın davranışının modellenmesinde Mohr-Coulomb (MC) model kullanılmıştır [24,28]. Ray, travers, alt balast ve taban zeminin malzeme özellikleri ise Jiang ve Nimbalkar [24] Lokomotif kısmında bulunan dingillerin her birinin yükü yaklaşık 170 kN, uç bojilerdeki dingil yükleri yaklaşık 120 kN ve bar vagonlarındaki dingil yükleri de yaklaşık 155 kN'dir.…”
Section: şEkil 1 Geliştirilen Nümerik Modelin Geometrisi Ve Boyutlarıunclassified
“…A suitable FEM approach depends on the required precision and the complexity of the problem [5]. 2D models can consider the discontinuities of track structure in either horizontal or longitudinal planes [23][24][25][26]. However, the real field geometries of track transition zones can be more complex and non-typical in both directions; for example, the embankment bridge approaches with the auxiliary rails representing the discontinuities in longitudinal and horizontal direction [27].…”
Section: Introductionmentioning
confidence: 99%